Strategic Analysis of Application of The Hazard Analysis Critical Control Point on “Bite and Bite Cakes Home Industry” in Sidoarjo, Indonesia - Muhammad Naufal Zhorif; Frizqa Ayu Bariqlana; Erwan Adi Saputro; Anugerah Dany Priyanto (Nusantara Science and Technology Proceedings, 2022)
This study presents the analysis of a food safety management system based on Hazard Analysis Critical Point (HACCP) principles and application in the home industry. Bite and Bite Cakes is a kind of private home industry that produces commercial flour-based food baked product and was established since 2017. This business uses social media as e-commerce strategies to promote and sell their products. This study aimed to evaluate and develop the HACCP plan in small food industry from production until distribution. An interview and observation were conducted to collect the data from the owners through directly observed during the production process. Three categories of food safety hazards were founded in brownies production line, specifically at biological, physical, and chemical agents. These concluded hazards showed that several steps are categorized as potential CCP, specifically the raw material receiving, baking, and packaging. Hopefully, these assessments of food safety management system could provide and improve the food safety and quality, especially in-home industry.